Optimalisasi Prolanis Berbasis Lima Pilar Untuk Pengendalian Hba1c Pada Pasien Diabetes Melitus Di Puskesmas Balowerti Kota Kediri - Agusta Dian E; Akbar Zulkifli; Gretta Hapsari Amalya; Shinta Meriza Aprillia; Dwi Puspito Adi; Fitaria Andrini (CV. ITTC INDONESIA, 2026)
Background: Type 2 Diabetes Mellitus (DM) is a noncommunicable disease with a growing global burden; Indonesia ranks fifth worldwide with an estimated 20.4 million people with diabetes aged 20–79 years (IDF, 2024).Objective: This community service activity aimed to optimize five-pillar-based Prolanis (Chronic Disease Management Program) implementation to improve the achievement of an effective HbA1c target (<7%) among elderly participants at Balowerti Community Health Center, Kediri City.Methods: The activity was conducted with 30 Prolanis participants through blood pressure and fasting blood glucose screening, chair exercise, interactive health education, and an interview questionnaire. HbA1c data from December 2025 and June 2026 were analyzed descriptively, including paired analysis to identify individual improvement trends. Results: Mean HbA1c in June 2026 was 7.14%, with 19 participants (54%) controlled and 16 (46%) uncontrolled. Paired analysis showed 18 participants (60%) with an improving trend and 12 (40%) worsening. The main barriers to glycemic control were the nutrition pillar (the 3J diet principle) and variable family support.Conclusion: Optimizing Prolanis requires strengthened structured nutrition education, continuous dietary mentoring, and reinforced family involvement to gradually increase the proportion of participants with controlled HbA1c toward BPJS Kesehatan's Controlled Prolanis Participant Ratio (RPPT) ≥70% standard.